Fermented green tea extract exhibits hypolipidaemic effects through the inhibition of pancreatic lipase and promotion of energy expenditure. Issue 2 (30th January 2017) - Seo, Dae-Bang; Jeong, Hyun Woo; Kim, Yeon-Ji; Kim, Sukyung; Kim, Jeongkee; Lee, Ji Hae; Joo, Kyungmi; Choi, Jin Kyu; Shin, Song Seok; Lee, Sung-Joon
Abstract: Hyperlipidaemia is a major cause of atherosclerosis and related CVD and can be prevented with natural substances. Previously, we reported that a novel Bacillus -fermented green tea (FGT) exerts anti-obesity and hypolipidaemic effects. This study further investigated the hypotriglyceridaemic and anti-obesogenic effects of FGT and its underlying mechanisms. FGT effectively inhibited pancreatic lipase activity in vitro (IC50, 0·48 mg/ml) and ameliorated postprandial lipaemia in rats (26 % reduction with 500 mg/kg FGT). In hypertriglyceridaemic hamsters, FGT administration significantly reduced plasma TAG levels. In mice, FGT administration (500 mg/kg) for 2 weeks augmented energy expenditure by 22 % through the induction of plasma serotonin, a neurotransmitter that modulates energy expenditure and mRNA expressions of lipid metabolism genes in peripheral tissues. Analysis of the gut microbiota showed that FGT reduced the proportion of the phylum Firmicutes in hamsters, which could further contribute to its anti-obesity effects. Collectively, these data demonstrate that FGT decreases plasma TAG levels via multiple mechanisms including inhibition of pancreatic lipase, augmentation of energy expenditure, induction of serotonin secretion and alteration of gut microbiota. These results suggest that FGT may be a useful natural agent for preventing hypertriglyceridaemia and obesity.